Medical pluralism and HIV/AIDS in South Africa : what are the barriers to collaboration between traditional healers and medical doctors? - Tugendhaft, Aviva (My University, 2010)
Objective The high prevalence rates of HIV/AIDS in South Africa clearly point towards the need to mobilise all available resources in order to adequately respond to the epidemic and its outcomes. It seems that strategies to date have not fully taken into account the plurality of available healing systems. It is estimated that a large percentage of the population, which has been disproportionately affected by the epidemic, makes use of Traditional Healers. In light of the severity of HIV/AIDS and its impact on society, it is necessary to explore options of collaboration between Allopathic and Traditional Medicine that may lead to more effective strategies. The literature on this topic in the context of Medical Pluralism in SA is scant and inadequate. The complexity of the issues involved has not been fully interrogated and an assessment of obstacles is lacking. This study therefore aims to investigate the barriers to effective collaboration, as well as the enabling factors that will facilitate a cooperative environment. Methods Qualitative research methods were used including documentary analysis of official policy on HIV/AIDS and Traditional Medicine as well as interviews and focus groups with Traditional Healers and Medical Doctors. Key findings The analysis of findings focuses on: 1. Government’s official position with regard to Traditional Medicine and its practitioners. 2. The way in which Traditional Healers are perceived by Medical Doctors in terms of the role they could play in addressing HIV/AIDS. 3. The beliefs and practices of Traditional Healers with regard to HIV/AIDS and their perception and attitude towards biomedicine